1997
DOI: 10.1006/jmbi.1997.1134
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a coronavirus ribosomal frameshift signal in Escherichia coli: influence of tRNA anticodon modification on frameshifting

Abstract: Eukaryotic ribosomal frameshift signals generally contain two elements, a heptanucleotide slippery sequence (XXXYYYN) and an RNA secondary structure, often an RNA pseudoknot, located downstream. Frameshifting takes place at the slippery sequence by simultaneous slippage of two ribosome-bound tRNAs. All of the tRNAs that are predicted to decode frameshift sites in the ribosomal A-site (XXXYYYN) possess a hypermodified base in the anticodon-loop and it is conceivable that these modifications play a role in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
79
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 60 publications
(83 reference statements)
9
79
0
Order By: Relevance
“…According to the simultaneous slippage model (Jacks et al 1988), −1 frameshifts occur after the A-site is filled, by simultaneous slippage of the tRNAs present in both A-and P-sites, that is prior to translocation. In general, our results (Table 3) and those of others (Hagervall et al 1993;Brierley et al 1997;Carlson et al 1999;Marczinke et al 2000) sug- gest that tRNA modifications have no or only a minor effect on −1 frameshifts. In fact, in some cases, the presence of the modified nucleoside actually stimulates −1 frameshifting (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…According to the simultaneous slippage model (Jacks et al 1988), −1 frameshifts occur after the A-site is filled, by simultaneous slippage of the tRNAs present in both A-and P-sites, that is prior to translocation. In general, our results (Table 3) and those of others (Hagervall et al 1993;Brierley et al 1997;Carlson et al 1999;Marczinke et al 2000) sug- gest that tRNA modifications have no or only a minor effect on −1 frameshifts. In fact, in some cases, the presence of the modified nucleoside actually stimulates −1 frameshifting (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, in E. coli, the s 2 -or the mnm 5 -group each has very little or no influence on −1 frameshifting at a U-UUA-AAG site, and the s 2 -group has no influence on −1 frameshifting at the U-UUA-AAA site (Brierley et al 1997). However, lack of the mnm 5 -group increases the −1 frameshifting at the slippery U-UUA-AAA sites twofold (Brierley et al 1997). Thus, contrary to the large impact of mnm 5 s 2 U34 to prevent +1 shifts, its role in −1 frameshifting is minor, and, in fact, in some cases the presence of it increases the −1 frameshift error.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The process of frameshifting was first described from studies of Rous sarcoma virus replication (220) and has been extensively defined in the MMTV and infectious bronchitis virus (IBV) (a coronavirus)] systems, although it occurs widely throughout other eukaryotic RNA viruses (151). Frameshift sites within the viral mRNA correspond to heptanucleotide sequences in which the mRNA slips 1 base with respect to the tRNAs in the A and P sites on the translating ribosome (40,108). The frameshift site, also known as the slippery site, allows the tRNA to move along the mRNA template by 1 base (forward or back) and reestablish codon-anticodon pairing, resulting in a stable ϩ1 or Ϫ1 reading frame shift.…”
Section: Mechanisms and Control Of Viral Mrna Translationmentioning
confidence: 99%
“…Thus, it has been suggested that hypomodified variants of these tRNAs may function to promote shifting by being less bulky and therefore more easily moved within the slippery site (186). However, this idea remains controversial, since other researchers have proposed that frameshifting is mediated by standard cellular tRNAs and is simply dependent on the strength of the codon-anticodon tRNA interaction (40,465). In either case, frameshifting requires a pseudoknot structure near the slippery site to stimulate the frameshifting events.…”
Section: Mechanisms and Control Of Viral Mrna Translationmentioning
confidence: 99%